Mycosins Are Required for the Stabilization of the ESX-1 and ESX-5 Type VII Secretion Membrane Complexes - Vincent J. C. van Winden (American Society for Microbiology, 2016)
ABSTRACT Pathogenic mycobacteria contain up to five type VII secretion (T7S) systems, ESX-1 to ESX-5. One of the conserved T7S components is the serine protease mycosin (MycP). Strikingly, whereas MycP is essential for secretion, the protease activity of MycP1 in Mycobacterium tuberculosis has been shown to be dispensable for secretion. The essential role of MycP therefore remains unclear. Here we show that MycP1 and MycP5 of M. marinum have similar phenotypes, confirming that MycP has a second unknown function that is essential for its T7S system. To investigate whether this role is related to proper functioning of the T7S membrane complex, we first analyzed the composition of the ESX-1 membrane complex and showed that this complex consists of EccBCDE1, similarly to what was previously shown for ESX-5. Surprisingly, while mycosins are not an integral part of these purified core complexes, we noticed that the stability of both the ESX-1 complex and the ESX-5 complex is compromised in the absence of their MycP subunit. Additional interaction studies showed that, although mycosins are not part of the central ESX membrane complex, they loosely associate with this complex. We hypothesize that this MycP association with the core membrane complex is crucial for the integrity and functioning of the T7S machinery. IMPORTANCE Among the major virulence factors of pathogenic mycobacteria are the type VII secretion (T7S) systems. Three of these systems, ESX-1, ESX-3, and ESX-5, have been shown to be crucial for virulence or viability. Here we describe the function of mycosin proteases, which are conserved components within these systems. We show that MycP1 and MycP5 have a second, proteolytic-independent function which is essential for the T7S system. We additionally found that this second essential role is related to the stabilization and proper functioning of their respective ESX membrane core complexes. Finally, we found that this is mediated by a loose association of MycP with the complex. Understanding the essential role of mycosins in type VII secretion systems, which play central roles in the virulence and viability of pathogenic mycobacteria, may provide new intervention strategies to treat tuberculosis.